Inhibitory Effect of Volatiles Emitted From Alcaligenes faecalis N1-4 on Aspergillus flavus and Aflatoxins in Storage - Gong, An-Dong; Wu, Nan-Nan; Kong, Xian-Wei; Zhang, Yi-Mei; Hu, Meng-Jun; Gong, Shuang-Jun; Dong, Fei-Yan; Wang, Jian-Hua; Zhao, Zhi-Yong; Liao, Yu-Cai (Frontiers in Microbiology, 2019)
Controlling aflatoxigenic Aspergillus flavus (Af) and aflatoxins in grains and food during storage are great challenge to humans worldwide. Alcaligenes faecalis N1-4 isolated from tea rhizosphere soil can produce abundant antifungal volatiles, and greatly inhibited the growth of Af in un-contacted face-to-face dual culture tests. Gas chromatography tandem mass spectrometry revealed that dimethyl disulfide (DMDS) and methyl isovalerate (MI) were two abundant compounds in the volatile profiles of N1-4. DMDS with the highest relative abundance (69.90%, to the total peak area) in N1-4 volatiles eventually prevented the conidia germination and mycelia growth of Af at 100 µL/L respectively. The concentration for MI against Af is 200 µL/L. Additionally, Real‑time Quantitative PCR analysis proved that the expression of 11 important genes in aflatoxin biosynthesis pathway were significantly reduced by these volatiles. And the Af disease and aflatoxins contamination in groundnut, maize, rice and soybean of high water activity were also completely inhibited by volatiles in storage. Scanning electron microscope further proved that Af conidia inoculated on peanuts surface were severely damage by volatiles from N1-4, and can not germinate to hyphae and conidiophore. Furthermore, strain N1-4 showed broad and effective antifungal activity to other 6 important plant pathogens including Fusarium graminearum, F. equiseti, Alternaria alternate, Botrytis cinerea, Aspergillus niger and Colletotrichum graminicola. Thus, we could deduce that Alcaligenes faecalis N1-4, and the produced volatile DMDS and MI, can be used as potential biocontrol agents in control Af and aflatoxins during storage. These results also expanded the resources for the screening of bio-active agents in controlling fungal pathogens and mycotoxins.